AN ANALYSIS ON THE STUDENTS COMPETENCE IN PREDICTING PICTURES ON READING TEXT AT SMA NEGERI 1 BARRU - Amalia Ramadhani; Eny Satriana; Wildan Burhanuddin (Journal of Language Testing and Assessment, 2022)
This research deals with a reading focused on analysis of the students competence in predicting pictures on reading descriptive text particularly in describe the object. The level of students analyzed is the XI Grade at SMA Negeri 1 Barru.This research used a descriptive quantitative method. The population of this research was  grade XI of the students that consist of 340 students at SMA Negeri 1 Barru. The sample of this research used purposive sampling was XI MIA 2 that consisted of 30 students. The instrument used in this research was picture and essay test.The result of this research was the competence in predicting pictures was very good. From 27 students or 90% got very good level. The second is good level, there were 2 students or 7% got good level. The third is low level, there were 1 students or 3% got low level. As well as their reading comprehension of the text with mean score 80.33. It can be conclude that the result of this research was appropriate with the theory which stated that pictures was useful for getting students to predict what is coming next in a lesson. It is also help the students can look at the picture and try to guess what it shows.